Study of the behavior of the credit portfolio of the popular and solidarity financial system of Manabí - Loor Alcívar, José Daniel (2023)
The financial system plays an important role within the economy by offering savings and credit products. The restrictions applied as a result of COVID-19 affected the normal development of activities in all sectors of the national economy and the Popular and Solidarity Financial System (SFPS) was no exception, which is why the purpose of this study was analyze the behavior of the SFPS credit portfolio in Savings and Credit Cooperatives (COAC) segment 1 of the province of Manabí during the period 2019-2021. A descriptive and field investigation was carried out with a qualitative approach, which made it possible to describe the main effects that these COAC'S had on the portfolio indicators, evidencing the slowdown in its growth and a decrease in the delinquency rate in the initial period. of the pandemic that occurred in 2020. The study demonstrated the important role of the SFPS regulatory bodies in issuing regulations for this sector, who must maintain constant training and updating regarding the application of methodologies and regulations that contribute to the sustainability and improvement of SFPS.